Virus reactivations after autologous hematopoietic stem cell transplantation detected by multiplex PCR assay. Issue 2 (27th July 2016) - Inazawa, Natsuko; Hori, Tsukasa; Nojima, Masanori; Saito, Makoto; Igarashi, Keita; Yamamoto, Masaki; Shimizu, Norio; Yoto, Yuko; Tsutsumi, Hiroyuki
Abstract : Several studies have indicated that viral reactivations following allogeneic hematopoietic stem cell transplantation (allo‐HSCT) are frequent, but viral reactivations after autologous HSCT (auto‐HSCT) have not been investigated in detail. We performed multiplex polymerase chain reaction (PCR) assay to examine multiple viral reactivations simultaneously in 24 patients undergoing auto‐HSCT between September 2010 and December 2012. Weekly whole blood samples were collected from pre‐ to 42 days post‐HSCT, and tested for the following 13 viruses; herpes simplex virus 1 (HSV‐1), HSV‐2, varicella‐zoster virus (VZV), Epstein–Barr virus (EBV), cytomegalovirus (CMV), human herpesvirus 6 (HHV‐6), HHV‐7, HHV‐8, adeno virus (ADV), BK virus (BKV), JC virus (JCV), parvovirus B19 (B19V), and hepatitis B virus (HBV).  Fifteen (63%) patients had at least one type of viral reactivation. HHV6 (n = 10; 41.7%) was most frequently detected followed by EBV (n = 7; 29.2%). HHV‐6 peaked on day 21 after HSCT and promptly declined. In addition, HBV, CMV, HHV7, and B19V were each detected in one patient. HHV6 reactivation was detected in almost half the auto‐HSCT patients, which was similar to the incidence in allo‐HSCT patients. The incidence of EBV was unexpectedly high. Viral infections in patients undergoing auto‐HSCT were higher than previously reported in other studies. Although there were no particular complications of viral infection, we should pay attention to possible viral reactivations in auto‐HSCT patients. J. Med. Virol. 89:358–362, 2017 . © 2016 Wiley Periodicals, Inc.